Toll-like receptor 1/2 activation reduces immunoglobulin free light chain production by multiple myeloma cells in the context of bone marrow stromal cells and fibronectin. - Jahan Abdi; Frank Redegeld (PLoS ONE)
Toll-like receptor (TLRs) activation in multiple myeloma (MM) cells induces heterogeneous functional responses including cell growth and proliferation, survival or apoptosis. These effects have been suggested to be partly due to increase in secretion of cytokines such as IL-6 or IFNα among others from MM cells following TLR activation. However, whether triggering of these receptors also modulates production of immunoglobulin free light chains (FLCs), which largely contribute to MM pathology, has not been investigated in MM cells before. This study explored the effect of TLR1/2 ligand (Pam3CSK4) alone or combined with bortezomib (BTZ) on production of FLCs in human myeloma cell lines, L363, OPM-2, U266 and NCI-H929. It also investigated the above effect when MM cells were exposed to bone marrow stromal cells (BMSCs) or fibronectin (FN). Adhesion to BMSCs or FN increased secretion of FLC in MM cells. Pam3CSK4 decreased FLC production, and this effect was enhanced in combination with BTZ but attenuated when MM cells adhered to BMSCs or FN. The findings of this study imply that activation of TLR1/2 downregulates FLC production in MM cells even in the context of bone marrow microenvironment components and suggest that targeting some TLRs such as TLR1/2 might have therapeutic potential.